(untitled) (Research, Society and Development, 2023)
Endodontic treatment has as main objective to restore the function of a dental element in the stomatognathic system, without harming the patient’s health. Through an effective disinfection of the root canals, which is obtained through chemical-mechanical preparation. However, it is known that the anatomy of the root canal system is complex and the instrumentation of the main canal leaves areas untouched, so that the lateral canals, isthmuses and branches depend mainly on the chemical effects of irrigants and intracanal medications. Therefore, the objective of the present work is to review the literature about the main irrigation solution activation systems and discuss their characteristics, indications and clinical protocols. Methodology of the present study, aimed at a literary review in which it was characterized by being a bibliographical research about the activation resources of irrigating solutions in endodontics, the research was carried out in the electronic databases PubMed, Scielo, Lilacs. The bibliographical survey was carried out during the months of 10 (October) 2022 to 5 (May) 2023. It was concluded, based on the literature review, it is possible to state that there is not, today, a single and totally effective protocol to be followed. However, it is essential to use systems and strategies that optimize disinfection to reach complex root canal structures.